2014
DOI: 10.1016/j.proeng.2014.11.140
|View full text |Cite
|
Sign up to set email alerts
|

Low Velocity Impact Damage in Composite Laminates Based on Waste Polyolefins

Abstract: Composite laminates based on polyolefin wastes coming from two different sources are compared with similar systems involving a virgin polypropylene in terms of damage behavior. In particular, this paper reports the response of film-stacked composite laminate plates subjected to falling weight impact tests. As expected, samples based on recycled polyolefins show lower impact parameters with respect to the latter ones even if a partial improvement of the performances can be obtained by modification of the matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Several studies have investigated the extent of damage on composite laminate when exposed to low-velocity impact based on stacking sequence [ 3 , 11 , 15 , 16 , 17 , 18 ]. To test the effects of low-velocity damage in composite laminates, Russo et al [ 19 ] subjected film-sacked composite laminate plates to a falling weight test to analyze the damage behavior of virgin polypropylene. They concluded that recycled polyolefins had lower impact parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the extent of damage on composite laminate when exposed to low-velocity impact based on stacking sequence [ 3 , 11 , 15 , 16 , 17 , 18 ]. To test the effects of low-velocity damage in composite laminates, Russo et al [ 19 ] subjected film-sacked composite laminate plates to a falling weight test to analyze the damage behavior of virgin polypropylene. They concluded that recycled polyolefins had lower impact parameters.…”
Section: Introductionmentioning
confidence: 99%
“…As SEM morphological studies confirmed, the impact results posited an enhancement in the interfacial adhesion to fiber breakage. Additionally, the prototypical dissipative procedure of damage improved under the testing conditions [ 19 ]. Similarly, Kwon et al [ 20 ] compared the mechanical performance of carbon fiber-reinforced polypropylene (CF/PP) and random fiber-reinforced polypropylene and their performance against a steel fender, with the results indicating that CF/PP lamination had imperfect resin impregnation.…”
Section: Introductionmentioning
confidence: 99%